2014
DOI: 10.1186/1471-2369-15-5
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic uremic syndrome following fire ant bites

Abstract: BackgroundHaemolytic-uremic syndrome (HUS) is a severe, life-threatening disease with symptoms such as haemolytic anaemia, renal failure, and a low platelet count. Possible aetiology includes bacterial infections, medication, post-hematopoietic cell transplantation, pregnancy, autoimmune disease, and acquired immunodeficiency syndrome.Case presentationWe report the case of a 21-year-old healthy man who developed acute renal failure caused by HUS. Typical symptoms of HUS combined with severe uraemia developed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…SW is characterized by the presence of a lucent zone in the lamina rara interna and it is the most frequent glomerular lesion attributed to endothelial damage [ 17 ]. SW has been reported in human cases of endothelial damage such as transplant glomerulopathy, thrombotic microangiopathy, or hemolytic uremic syndrome, in which evolving chronicity is occasionally accompanied by segmental glomerular sclerosis [ 11 , 16 , 19 , 26 ]. Therefore, it is quite conceivable that podocyte and glomerular endothelial injury are involved in the development of FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…SW is characterized by the presence of a lucent zone in the lamina rara interna and it is the most frequent glomerular lesion attributed to endothelial damage [ 17 ]. SW has been reported in human cases of endothelial damage such as transplant glomerulopathy, thrombotic microangiopathy, or hemolytic uremic syndrome, in which evolving chronicity is occasionally accompanied by segmental glomerular sclerosis [ 11 , 16 , 19 , 26 ]. Therefore, it is quite conceivable that podocyte and glomerular endothelial injury are involved in the development of FSGS.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients (17 to 56%) develop a large local reaction consisting of an extremely large and pruritic lesion persisting for up to 72 h [13]. IgE-mediated severe allergic reactions following IFA stings are well documented and sometimes even lead to severe endorgan damage, including rhabdomyolysis, renal failure, and neurotoxic effects, which can also be induced by direct toxic effects of multiple ant stings [14][15][16][17].…”
Section: Yellow Fever Mosquito (Aedes Aegypti)mentioning
confidence: 99%
“…Later surveys over the period [2005][2006][2007][2008][2009][2010][2011] showed that more than one-third of people in infested areas had been stung and again nearly 1% of victims experienced severe allergic reactions with some deaths recorded as a result (Xu et al 2012). In Taiwan, several cases of severe reactions to stings have been reported (Chen et al 2005;Lee et al 2014).…”
Section: Hea Lthmentioning
confidence: 99%